The Meaning and Purpose of “The First Day of The Week” in 1 Cor 16:1-4 - Rudolf Weindra Sagala (Jurnal Koinonia, 2022)
For centuries, the word "κατα μιαν σαββατων’ " which meaning "first day of the week" in 1 Corinthians 16:2, has been a contentious term in Christianity. Many Christian scholars have accepted the phrase "first day of the week" as proof that early Christians observed Sunday as a day of worship. On the other hand, due to the context of the text, some scholars consider that this statement does allude to retaining Sunday as a day of worship, but for a different reason. As a result, the study's goal is to figure out what day early Christians worshiped and what it means today. In order to comprehend the meaning of the phrase "κατα μιαν σαββατων" and avoid misunderstanding among Christians, the author attempted to analyze the meaning and intent of that phrase through research. The meaning of each Greek word in the texts, the grammatical and syntactical structure of the texts, the broader context of the problematic phrase, and the use of extra Biblical study. The finding of the study shows that that the meaning of "first day of the week" refers to Sunday as the first day of the week, since in Greek Sabbath also means a week. However, the language of 1 Corinthians 16:2 does not mention worship; rather, it instructs members to lay aside an amount for the Jerusalem collection on the first day of the week at home .